Odpowiedzi

2010-03-29T18:22:01+02:00
3/x-2=4/2x+1 || mnożę przez (x-2) i (2x+1)
3(2x+1) = 4(x-2)
6x + 3 = 4x - 8
2x = -11
x = -5,5

2/3=3x+2/2x-2 ||mnożę przez 3 oraz (2x-2)
2(2x-2) = 3(3x+2)
4x - 4 = 9x + 6
-5x = 10
x = -2

6x-1/x+1=2,3/1,2 |mnożę przez 1,2 oraz x+1
1,2*(6x-1) = 2,3(x+1)
7,2x - 1,2 = 2,3x + 2,3
4,9x = 3,5
x = 3,5 / 4,9

-x/3x-1=2x/1-6x |mnożę przez 3x-1 oraz 1-6x
-x(1-6x) = 2x(3x-1)
-x + 6xx = 6xx - 2
-x = -2
x = 2
zauważ, że x może też równać się 0, wtedy 0=0
tutaj są 2 rozwiązania ---> x=2 ∨ x=0